PERSEPSI KONSUMEN SEBAGAI MEDIATOR ANTARA KEPRIBADIAN MEREK DAN PENGALAMAN MEREK: STUDI PADA AGROINDUSTRI OLEH-OLEH MAKANAN MILIK SELEBRITI DI MALANG, INDONESIA (Consumer Perception as a Mediator Between Brand Personality and Brand Experience: A Study of Celebrity-Owned Souvenir Food Agroindustries in Malang, Indonesia) - Ramadhani, Mirza; Riana, Fitria Dina; Hartati Wahyuningtyas, Agustina Shinta; Illahi, Rhochmad Wahyu; Anam, M. Khairul (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
In recent years, culinary tourism in tourist destinations has become a trend among global travelers. The development of tourism has also brought a shift in motivation from travel-based tourism to shopping tourism. However, it is known that there is considerable competition among culinary souvenir centers. Meanwhile, brand preferences are highly dynamic, making it essential for managers to consider them in efforts to increase customer satisfaction, encourage repeat visits, or even generate word-of-mouth intentions. This study aims to analyze the influence of brand personality, perceived coolness, and perceived service quality on brand experience. The research location was selected purposively, focusing on culinary souvenir centers in Malang City. The sampling technique used was non-probability sampling with purposive sampling method, involving a total of 100 respondents. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via WarpPLS 7.0 software. The results show that there is a significant relationship between brand personality and brand experience through perceived coolness and perceived service quality. However, the relationship between perceived service quality and brand experience was found to be insignificant. Keywords: Brand Personality, Perceived Coolness, Perceived Service Quality, Brand Experience.